REALISATION OF LANGUAGE VARIATION THROUGH CODE MIXING IN SATU PERSEN-INDONESIAN LIFE SCHOOL ON YOUTUBE.COM - Ela Martisa; Nasruddin Nasruddin; Ansor Putra; Amiruddin Eso (MARAS: Jurnal Penelitian Multidisiplin, 2023)
The study is aimed to describe the types and the functions of code mixing in Satu Persen-Indonesian Life School Youtube channel. Thelander’s theory used to describe the types of code mixing and Marasigan’s theory used to analyze the functions of code mixing. There are two data sources in the research; the first data are three videos from Satu Persen on Youtube as primary data and a video script for each video as secondary data. The study used the descriptive qualitative method. The data were collected by watching, downloading, transcribing, identifying, coding, and classifying the data. The data analysis was done by presenting, describing, interpreting and concluding the data. The finding shows that there are fifteen data about code mixing in Satu Persen’s videos. It reveals that there are six types of code-mixing found in the videos namely word insertion, phrase insertion, hybrid insertion, repetition insertion, idiom insertion and clause insertion. Meanwhile, the functions of code mixing used are to quote somebody else, interjection, addressee specification, repetition, message qualification, personalization and objectification and facility expression.